2017
DOI: 10.1097/qad.0000000000001299
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in HIV-infected youth is associated with decreased mitochondrial respiration

Abstract: Objective:To identify relationships between insulin resistance (IR) and mitochondrial respiration in perinatally HIV-infected youth.Design:Case–control study.Methods:Mitochondrial respiration was assessed in perinatally HIV-infected youth in Tanner stages 2–5, 25 youth with IR (IR+) and 50 without IR (IR−) who were enrolled in the Pediatric HIV/AIDS Cohort Study. IR was defined as a homeostatic model of assessment for IR value at least 4.0. A novel, high-throughput oximetry method was used to evaluate cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
0
27
1
Order By: Relevance
“…The underlying reason for higher l ‐lactate concentrations in ponies compared to horses is still unknown. In people, increases in l ‐lactate concentrations are closely associated with fasting glucose and insulin concentrations, insulin resistance, and type 2 diabetes . Increases in l ‐lactate concentration are predictive of development of insulin resistance and might be an independent risk factor for the development of type 2 diabetes .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The underlying reason for higher l ‐lactate concentrations in ponies compared to horses is still unknown. In people, increases in l ‐lactate concentrations are closely associated with fasting glucose and insulin concentrations, insulin resistance, and type 2 diabetes . Increases in l ‐lactate concentration are predictive of development of insulin resistance and might be an independent risk factor for the development of type 2 diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the increased l ‐lactate concentrations in people is still unknown, but a decreased aerobic capacity has been suggested . A low oxidative capacity due to impaired mitochondrial phosphorylation has been associated with subclinical or clinical insulin resistance . Although it is currently unknown whether the low oxidative capacity is a consequence or cause of insulin resistance, recent studies have suggested that a low oxidative capacity may precede insulin resistance and diabetes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in non-mitochondrial respiration suggests mitochondria dysfunction leading to a compromised ETC. Takemoto et al recently reported that HIV-infected youth with insulin resistance had lower mitochondrial respiratory parameters and concluded that disordered mitochondrial respiration may be a potential mechanism of insulin resistant in HIV-infected youth (35).…”
Section: Discussionmentioning
confidence: 99%